Burnout Syndrome and alcohol consumption in prison employees - Campos, Juliana Alvares Duarte Bonini; Schneider, Valéria; Bonafé, Fernanda Salloume Sampaio; Oliveira, Raquel Velez; Maroco, João (Associação Brasileira de Saúde Coletiva, 2016)
ABSTRACT:Objective:The aims of this study were to estimate the association between an at-risk drinking pattern and sociodemographic variables, and to compare the mean scores of the factors associated with the Burnout Syndrome, according to the alcohol consumption pattern in staff members from two Brazilian prisons.Methods:A cross-sectional study was developed with 339 participants (response rate = 63.8%). The instruments used were a sociodemographic questionnaire, the Alcohol Use Disorders Identification Test (AUDIT), and the Maslach Burnout Inventory - General Survey (MBI-GS).Results:The participants' average age was 40.2 (SD = 8.8) years, and 81.0% were male. Among 78.5% of participants (95%CI 74.1 - 82.8) reported consuming alcoholic beverages. The prevalence of at-risk drinking behavior in the sample was 22.4% (95%CI 18.0 - 26.9), and of the Burnout Syndrome was 14.6% (95%CI 10.8 - 18.4). We observed a significant association between at-risk drinking behavior with gender, higher risk for men (OR = 7.32, p < 0.001), smoking, increased risk for smokers (OR = 2.77, p < 0.001), and religious practice, showing lower risks for religion practitioners (OR = 0.364, p < 0.001). We noticed significantly higher mean scores (p < 0.001) of emotional exhaustion and cynicism, and lower scores of professional achievement among individuals who reported consuming alcoholic beverages.Conclusion:Men who smoke were more likely to develop an at-risk drinking pattern, while religion is presented as a protective factor. Individuals who consume alcohol were more affected by the different factors of the Burnout Syndrome.

RESUMO:Objetivo:Estimar a associação entre o padrão de beber com risco e as variáveis sociodemográficas, e comparar os escores médios dos fatores relacionados com a Síndrome de Burnout , de acordo com o padrão do consumo de álcool em funcionários de duas prisões brasileiras.Métodos:Trata-se de um estudo transversal, desenvolvido com 339 participantes (taxa de resposta de 63,8%). Os instrumentos utilizados foram um questionário sociodemográfico, o Teste para Identificação de Problemas Relacionados ao Uso de Álcool (AUDIT) e o Inventário de Burnout de Maslach - Forma Geral (MBI-GS).Resultados:A média de idade dos participantes foi de 40,2 (DP = 8,8) anos, e 81,1% eram do sexo masculino. Um total de 78,5% dos participantes (IC95% 74,1 - 82,8) relatou consumir bebidas alcoólicas. A prevalência do comportamento de beber com risco na amostra foi de 22,4% (IC95% 18,0 - 26,9) e a da Síndrome de Burnout foi de 14,6% (IC95% 10,8 - 18,4). Observou-se associação significativa entre o comportamento de beber com risco com o gênero, o maior risco para os homens (OR = 7,32, p < 0,001), o tabagismo, risco aumentado para os fumantes (OR = 2,77, p < 0,001) e a prática religiosa, mostrando menor risco para os praticantes de religião (OR = 0,364, p < 0,001). Notaram-se escores médios (p < 0,001) mais altos de exaustão emocional e cinismo, e menor pontuação de eficácia profissional entre os indivíduos que relataram consumir bebidas alcoólicas.Conclusão:Homens fumantes foram os mais propensos a desenvolverem um padrão de beber com risco, enquanto a religião é apresentada como um fator protetor. Os indivíduos que consomem álcool foram os mais afetados pelos diferentes fatores da Síndrome de Burnout .
Síndrome de Burnout e consumo de álcool em agentes penitenciários
Keywords: Alcoholism; Burnout, Professional; Risk; Gender; Smoking; Religion.; Alcoolismo; Esgotamento profissional; Risco; Gênero; Tabagismo; Religião.